Non‐celiac gluten sensitivity: clinical relevance and recommendations for future research. Issue 11 (12th August 2013) - Mooney, P. D.; Aziz, I.; Sanders, D. S.
Abstract Background There has been increasing interest in the entity of Non‐Celiac Gluten Sensitivity (NCGS) in recent years; however, it still remains a controversial topic and its pathogenesis is not well understood. Celiac Disease, in contrast, is a well‐studied condition that has become increasingly recognized as a prevalent condition arising from a heightened immunological response to gluten. Wheat allergy is an IgE‐mediated condition capable of causing a variety of gastrointestinal symptoms. However, the number of patients who have neither celiac disease nor wheat allergy, but appear to derive benefit from a gluten‐free diet, is also increasing substantially. The use of the term NCGS as a way of describing this condition has become increasingly prevalent in recent years. Purpose In this review, we will focus on gastrointestinal manifestations of NCGS and discuss the evidence for the condition and its putative pathogenesis. We will discuss areas of controversy and areas for potential future research.